Kinerja Pegawai Dalam Meningkatkan Kualitas Pelayanan Masyarakat di Kantor Kelurahan Sempaja Selatan - Trisna Alan Pasoso; Rita Kalalinggi; Muhammad Jamal (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
This study aims to analyze and describe the work benchmarks of civil servants or state civil servants in improving the quality of service to the community at the Sempaja Selatan Sub-District Office and then the community's opinion of community services at the Kelurahan Office. The location of the research was carried out at the South Sempaja Village Office, North Samarinda District, Samarinda City. This type of research uses descriptive qualitative. Data collection was carried out through library and field research using observation, interview and documentation methods. Data were analyzed by descriptive qualitative. Based on the data developed by Miles, Huberman and Saldana, the authors did several things, namely collecting data, summarizing the data, then presenting the data, then drawing conclusions according to the theory of interactive data analysis. The results of this study indicate that the benchmark for the work of state civil servants or civil servants in improving the quality of service to the community at the Sempaja Selatan Village Office has been going quite well. This was obtained based on the results of research through actions taken by employees or state civil servants who carry out policies in providing services to residents of the South Sempaja Village, North Samarinda District, Samarinda City, as measured using dimensions/indicators Tangible, Reliability, Responsivenes, Assurance and Empathy. Furthermore, there are also several factors that influence the work benchmarks of state civil servants or apparatus in the implementation of services to the community at the Sempaja Selatan Village Office, namely the factor of the use of assistive devices and the factor of the place of service.